Penggunaan media dalam pembelajaran Tema 7 Indahnya Keragaman di Negeriku ditinjau dari gaya belajar siswa di kelas IV sekolah dasar - Kinasih, Aprilia Anggraini Puspa; Chumdari, Chumdari; Karsono, Karsono (Didaktika Dwija Indria, 2021)
This research to analyze the used of learning media and conformity between the learning media used in Theme 7 with the learning style of students in grade IV Elementary School. The research method used was descriptive qualitative. The reseacrh subjects were teachers and students of grade IV F Ta’mirul Islam Elementary School. The learning styles distinguished in visual, audiotorial and kinesthetic. The results of this research show that the media used in learning Theme 7 was suitable and in accordance with the principles and considerations of learning media selection. From 24 students, 12 students with visual learning style, 7 students with audiotorial learning style, and 5 students with kinesthetic learning style. The conclusion of this research was learning media used in Theme 7 facilitates more visual learning styles, but there are also learning media that facilitate audiotorial learning styles and kinesthetic learning styles. The implication of this research can increase knowledge about the use of learning media that is reviewed from learning style and can encaurage teachers to pay attention to consideration in the use of learning media especially learning style of students. Keywords: Learning Media, Thematic Learning, Theme 7 Indahnya Keragaman di Negeriku, Elementary School,  and Learning Style of Students.